ETHNOSEMANTICS STUDY OFLEXICON “KUBURAN”IN THE TORAJA PEOPLE - Hasmawati Hasmawati; Yusri Yusri; Alifia Masitha Dewi; Jamaluddin Gesrianto (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This research aims to explain the Toraja people’s perspectives regarding the lexicon of kuburan existed in their area. This is a qualitative research using the ethnosemantic approach. Data related to the lexicon of kuburanin the Toraja people were collected by interviewing the natives and traditional leaders there. The data collected then were analyzed using the componential analysis to find out the features from each lexicon of kuburan, so then it can be discovered how the cultural influences of the Toraja people affect the various lexicons of kuburan. The result of this research shows that there are nine lexemes of kuburanknown by the Toraja people, such as liangsilli, liangerong, liang toke, liangpak, tangdan, patani, lamunan, and pasillirankayu. These nine lexemes can be classified based on their social stratification level, age category, and any shapes or positions of the grave. Generally, each lexeme has differences in their function and features. The Toraja culture considers death as the orientation in life. Hence, they relate many things to death, and one of them is grave.